2008
DOI: 10.1310/tsr1504-295
|View full text |Cite
|
Sign up to set email alerts
|

Community-Based Stroke Information for Clients with Stroke and Their Carers: Is There Congruency Between Actual and Recommended Practice?

Abstract: Stroke is a leading cause of death and disability in the Western world, 1-3 with up to two thirds of stroke survivors living with some level of disability. 1,4 The provision of information is recognised as a key feature of poststroke management for clients with stroke, their carers, and their families, [5][6][7] and it can improve client and carer knowledge, reduce client depression, and increase some aspects of client satisfaction. 8 However, details of postdischarge information provision for community-dwelli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 66 publications
0
17
0
Order By: Relevance
“…Because stroke information needs continue to change over time [4,5,7,8], it is possible that as patients and carers become disconnected from the hospital service, that their preferences for receiving this information also change. Our recent study found that community-based services most frequently reported using an interactive delivery style and talking through written information in providing stroke information to patients and their carers [37], but whether this is suitable to stroke patients and their carers in the community is yet to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Because stroke information needs continue to change over time [4,5,7,8], it is possible that as patients and carers become disconnected from the hospital service, that their preferences for receiving this information also change. Our recent study found that community-based services most frequently reported using an interactive delivery style and talking through written information in providing stroke information to patients and their carers [37], but whether this is suitable to stroke patients and their carers in the community is yet to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…The design of the education and support package was informed by recommendations from the literature, 25 and previous research by the author team which explored current practice gaps, 25 patient and carer preferences for receiving information 19 and potential barriers to information provision. 26 The health professional providing the package was the lead author, who is an occupational therapist with clinical experience in stroke rehabilitation; however, the intervention was designed so that it could be provided by any health professional who has knowledge and experience in stroke management.…”
Section: Interventionmentioning
confidence: 99%
“…37 Stroke patients, for example, have previously identified that it would be helpful to receive follow-up visits or follow-up telephone calls from health professionals. 19 People with aphasia have also reported receiving relevant, useful, and easy-to-understand information by attending education programs run by multidisciplinary health care staff.…”
Section: Limitations and Further Researchmentioning
confidence: 99%